Fetal Exposure to Risky Drugs: Analysis of Antenatal Clinic Prescriptions in a Nigerian Tertiary Care Hospital - Onah, Paul Otor; Idoko, Catherine Chioma; Abdulateef, Siyaka (Faculty of Medicine Universitas Padjadjaran, 2023)
Objective: To assess fetal outcomes after in-utero exposure to unsafe drugs.Methods: This was a retrospective cohort study using data from medical records of pregnant women who received antenatal care over a two-year period (2019/2020). Inclusion was based on identification of prescription of potentially risky medications during pregnancy. Medication records, as well as delivery data, were extracted for analysis. The Australian drug evaluation committee classification system of risky medications was used for analysis.Results: Results showed that 44 – 65% of medicines prescribed in pregnancy carry significant risks to fetal wellbeing. Fetal outcomes showed high levels of low birth weight, still birth, and early neonatal death. The common medicines prescribed irrationally in pregnancy were, among others, antibiotics, ACEIs, NSAIDs, Biguanides, and opiates, all of which are associated with adverse fetal outcomes.Conclusion: There is a high level of fetal exposure to risky medications and adverse delivery outcomes. There is a need to improve prescription through prescriber training and awareness raising on existing guidelines on good prescribing practice for pregnant women.